Translation Shift Of Preposition Phrase In Kopkamtib Operation Chapter VIII And IX - Pebri Prandika Putra (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
The objective of this study was to determine the use of translation shift of preposition phrase in the Kopkamtib Operation Chapter VIII and IX. The translation shift that occurred in the data collected by the researcher was a category shift consisting of unit shift, intersystem shift, class shift and also structure shift. The researcher conducted a comprehensive analysis of Chapters VIII and IX in this book to find the occurrence of translation shifts. The research method used by the researcher is a qualitative method with a content analysis approach. The results of this study indicate that there are 18 shift of preposition phrase data found by researchers randomly. Translation Shift that occur are there are 8 data belonged to structure shift, 4 data belonged to intersystem shift, 3 data belonged to class shift and 3 data belonged to unit shift. This study concludes that a translation shift is something that must happen and cannot be avoided in the process of translating a text. But, although there were translation shift and semantic transition that happened in this book, it didn’t make so many problems in the quality and quantity of the text.